Legal Analysis Regarding the Application of Criminal Penalties for Perpetrators of Cybercrime - Budi Setiaji; Mhd Azhali Siregar; T. Riza Zarzani (PT. Sinergi Legal Publisher, 2025)
The purpose of writing this isTo determine the types of cybercrime that frequently occur and to determine law enforcement against perpetrators of cybercrime, using qualitative research methods. Cybercrime, or what we often hear as cybercrime, can be found regulated in the ITE Law and its amendments. The various types of internet crimes are regulated in the ITE Law. Before the ITE Law, cybercrime cases in Indonesia were tried using analogies to articles that had elements that matched the Criminal Code, so that criminal penalties for cybercrime perpetrators used the Criminal Code, abbreviated as the KUHP. In the KUHP, criminal provisions in cases of cybercrime in the form of phishing can be applied based on Article 378 of the KUHP. In Indonesia itself, cybercrime is regulated in Law Number 19 of 2016, an amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions.